2020
DOI: 10.1002/cbf.3572
|View full text |Cite
|
Sign up to set email alerts
|

Propofol induces oxidative stress and apoptosis in vitro via regulating miR‐363‐3p/CREB signalling axis

Abstract: Propofol, a generally used anaesthetic in patients care, has been proven to induce neurotoxicity. Studies have shown that miR-363-3p was closely related to neurological dysfunction, and the up-regulated miR-363-3p was recognized to be participate in propofol-induced neurotoxicity. However, the mechanisms and functions of miR-363-3p in propofol-induced neurotoxicity remain rarely reported. The aim of our research was to clarify the potential effects of miR-363-3p in neurotoxicity induced by propofol. SH-SY5Y ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…miR‐363 is a predictive, diagnostic, and prognostic biomarker for type 2 diabetes 47 . In addition, miR‐363 is able to suppress the pro‑inflammatory cytokine levels in cerebral ischemia/reperfusion injury 48 and moderate oxidative stress in the context of propofol‐induced neurotoxicity 49 . Our experimentation suggested miR‐363‐5p was downregulated in HG‐induced H9C2 cells and negatively regulated Hmgcs2, and miR‐363‐5p overexpression attenuated HG‐induced cell injury as evidenced by decreased LDH release, apoptosis, inflammation, and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…miR‐363 is a predictive, diagnostic, and prognostic biomarker for type 2 diabetes 47 . In addition, miR‐363 is able to suppress the pro‑inflammatory cytokine levels in cerebral ischemia/reperfusion injury 48 and moderate oxidative stress in the context of propofol‐induced neurotoxicity 49 . Our experimentation suggested miR‐363‐5p was downregulated in HG‐induced H9C2 cells and negatively regulated Hmgcs2, and miR‐363‐5p overexpression attenuated HG‐induced cell injury as evidenced by decreased LDH release, apoptosis, inflammation, and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Impairment of antioxidant defense mechanisms like SOD is additionally a contributing element in the occurrence of oxidative harm. [43][44][45] Earlier investigations have demonstrated that NBP mitigates the deterioration of cognitive abilities induced by neuroin ammation through its inhibition in rats with diabetes. 35 Nevertheless, the previous studies have not provided a comprehensive explanation of the potential mechanisms through which NBP enhances postoperative cognitive dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…45 The expression of miR-363-3p and miR-34a in SH-SY5Y cells was dysregulated after propofol treatment, resulting in a decrease in the cell survival rate. 46,47 Propofol can cause neuronal injury during brain development by causing an imbalance of miRNA expression. 10,27,48 Zhu et al exposed hippocampal neurons of neonatal rats to 50 μM propofol for 6 h. PCR showed that after propofol treatment, the expression of miR-455-3p decreased and the expression of its target protein EphA4 increased, leading to a decrease in neuronal proliferation and an increase in apoptosis.…”
Section: Noncoding Rnamentioning
confidence: 99%
“…45 The expression of miR-363-3p and miR-34a in SH-SY5Y cells was dysregulated after propofol treatment, resulting in a decrease in the cell survival rate. 46,47 Propofol can cause neuronal injury during brain development by causing an imbalance of miRNA expression. 10,27,48 Zhu et al .…”
Section: The Mechanism Of Propofol On Brain Damage During Developmentmentioning
confidence: 99%